2015
DOI: 10.1111/his.12556
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker expression and druggable gene alterations for development of an appropriate therapeutic protocol for pulmonary adenosquamous carcinoma

Abstract: In ASC, drug response-specific gene alterations could occur in both AC and SCC components, suggesting that patients with confirmed or suspected ASC should undergo further testing for driver gene analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Because EGFR mutation is the most common genomic anomaly in ASC, some studies ( 4 , 15 ) have focused on the efficiency of EGFR-TKIs in EGFR-positive ASC patients and found that ASC patients had similar efficacy to EGFR TKI compared with adenocarcinoma. Despite the presence of ALK-positive cases and molecular profiling studies of ASC ( 2 , 4 , 16 , 17 ), only a small number of ALK-TKI therapies for EML4-ALK fusion ASC patients have been reported ( 5 ), no non-classical ALK fusions have been reported in ASC. Echinoderm microtubule-associated protein-like 4 (EML4)-ALK is the canonical and most common ALK gene arrangement found in NSCLC, by which multiple EML4 breakpoints fuse in frame with the kinase domain of ALK ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because EGFR mutation is the most common genomic anomaly in ASC, some studies ( 4 , 15 ) have focused on the efficiency of EGFR-TKIs in EGFR-positive ASC patients and found that ASC patients had similar efficacy to EGFR TKI compared with adenocarcinoma. Despite the presence of ALK-positive cases and molecular profiling studies of ASC ( 2 , 4 , 16 , 17 ), only a small number of ALK-TKI therapies for EML4-ALK fusion ASC patients have been reported ( 5 ), no non-classical ALK fusions have been reported in ASC. Echinoderm microtubule-associated protein-like 4 (EML4)-ALK is the canonical and most common ALK gene arrangement found in NSCLC, by which multiple EML4 breakpoints fuse in frame with the kinase domain of ALK ( 18 ).…”
Section: Discussionmentioning
confidence: 99%